Turicibacter and Acidaminococcus predict immune-related adverse events and efficacy of immune checkpoint inhibitor - Hamada, Kazuyuki; Isobe, Junya; Hattori, Kouya; Hosonuma, Masahiro; Baba, Yuta; Murayama, Masakazu; Narikawa, Yoichiro; Toyoda, Hitoshi; Funayama, Eiji; Tajima, Kohei; Shida, Midori; Hirasawa, Yuya; et al. (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors have had a major impact on cancer treatment. Gut microbiota plays a major role in the cancer microenvironment, affecting treatment response. The gut microbiota is highly individual, and varies with factors, such as age and race. Gut microbiota composition in Japanese cancer patients and the efficacy of immunotherapy remain unknown. Therefore, we investigated the gut microbiota of 26 patients with solid tumors prior to immune checkpoint inhibitor monotherapy to identify bacteria involved in the efficacy of these drugs and immune-related adverse events (irAEs). In this study, the genera Prevotella and Parabacteroides were relatively common in the group showing efficacy towards the anti-PD-1 antibody treatment (effective group). The proportions of Catenibacterium (P = 0.022) and Turicibacter (P = 0.049) were significantly higher in the effective group than in the ineffective group. In addition, the proportion of Desulfovibrion (P = 0.033) was significantly higher in the ineffective group. Next, they were divided into irAE and non-irAE groups. The proportions of Turicibacter (P = 0.001) and Acidaminococcus (P = 0.001) were significantly higher in the group with irAEs than in those without, while the proportions of Blautia (P = 0.013) and the unclassified Clostridiales (P = 0.027) were significantly higher in the group without irAEs than those with. Furthermore, within the Effective group, Acidaminococcus and Turicibacter (both P = 0.001) were more abundant in the subgroup with irAEs than in those without them. In contrast, Blautia (P = 0.021) and Bilophila (P= 0.033) were statistically significantly more common in those without irAEs. Thus, the analysis of the gut microbiota may provide future predictive markers for the efficacy of cancer immunotherapy or the selection of candidates for fecal transplantation for cancer immunotherapy.